Evaluation of the Knowledge Sharing Process on the Ministry of Education Website in the Kingdom of Saudi Arabia: A Case Study - Mahnabi, Mona Ali (Journal of Humanities & Social Sciences, 2023)
The study aimed to clarify the concept and review the literature on the subject of knowledge sharing and extract a list of factors for evaluating knowledge sharing. The study also aimed to evaluate the knowledge sharing process for the website of the Ministry of Education in the Kingdom of Saudi Arabia. The content analysis approach was used to review scientific studies and extract knowledge sharing factors. The case study approach was also used to study the ministry’s website and apply knowledge sharing factors to it. One of the most important results of the study was that the ministry got (71%) in the knowledge sharing process. It is considered a good percentage and indicates the ministry’s interest in exchanging and sharing knowledge, but there is a shortcoming in providing means of participation among its employees and encouraging participation and exchange of experiences through the website. The Ministry is a culture that encourages the exchange of experiences and knowledge, and that The Ministry supports building mutual trust among employees to share knowledge.